2004
DOI: 10.1023/b:hrev.0000011392.03037.7e
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Interaction Between Matrix Metalloproteinase Activity and Adverse Myocardial Remodeling

Abstract: The process of cardiac remodeling in response to cardiac injury and/or persistent elevations in wall stress generally relates to the progressive changes that occur in ventricular chamber dimensions and the various components of the myocardium, in particular the cardiomyocytes and the extracellular matrix. Volume overload, pressure overload or myocardial injury produces a sustained abnormal elevation in myocardial wall stress which initiates cardiac remodeling that frequently results in ventricular decompensati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
82
1
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(88 citation statements)
references
References 59 publications
1
82
1
4
Order By: Relevance
“…12 In cardiac hypertrophy, it has been shown that the overall MMP gelatinolytic activity is increased and has crucial roles in the development of LVH and in the progression to decompensated LVH and heart failure. 6,7,28 Although our results suggesting a protective role for a MMP-2 polymorphism and haplotype associated with higher MMP-2 expression may seem paradoxical, little is known about the specific role for each MMP in this process and the possible signalling pathways that depend on them. 29 In this respect, transgenic models have contributed to the understanding of the roles for MMPs in LVH, and MMP-2 knockout mice present interesting reductions in LVH and its complications in models of heart hypertrophy.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…12 In cardiac hypertrophy, it has been shown that the overall MMP gelatinolytic activity is increased and has crucial roles in the development of LVH and in the progression to decompensated LVH and heart failure. 6,7,28 Although our results suggesting a protective role for a MMP-2 polymorphism and haplotype associated with higher MMP-2 expression may seem paradoxical, little is known about the specific role for each MMP in this process and the possible signalling pathways that depend on them. 29 In this respect, transgenic models have contributed to the understanding of the roles for MMPs in LVH, and MMP-2 knockout mice present interesting reductions in LVH and its complications in models of heart hypertrophy.…”
Section: Discussioncontrasting
confidence: 61%
“…6,7,9 Given the relevance of MMP-2 in these processes, functional genetic polymorphisms of this gene may affect the prevalence of LVH in hypertensive patients. This is the first report to show a protective effect associated with the CC genotype of the C À1306 T polymorphism against increases in EDD and LVMI in hypertensive subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disruption of the collagen matrix by increased MMP activity leads to increased stress for the cardiomyocytes, and therefore leads to further hypertrophy and remodeling [24]. In addition, this dissociation of collagen bundles by MMPs simulates further collagen synthesis through transcriptional activation of the corresponding genes [24]. The role of collagen in the resistance of the ventricular wall against rupture is further supported by the observation that transgenic mice with cardiac over-expression of the β 2 -adrenergic receptor have a lower rate of rupture compared to wild type mice, which correlates with a higher accumulation of interstitial collagen in the transgenic animal [25].…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…Among the multiple forms of MMPs, the gelatinases MMP2 and MMP9 are expressed both in cardiac fibroblasts and in myocytes, and can degrade several types of collagen (including the types 1 and 3) [23]. Disruption of the collagen matrix by increased MMP activity leads to increased stress for the cardiomyocytes, and therefore leads to further hypertrophy and remodeling [24]. In addition, this dissociation of collagen bundles by MMPs simulates further collagen synthesis through transcriptional activation of the corresponding genes [24].…”
mentioning
confidence: 99%